Effect of Weight-Reduction in Obese Mice Lacking Toll-Like Receptor 5 and C57BL/6 Mice Fed a Low-Fat Diet. (23rd November 2015) - Wu, Shao-Chun; Rau, Cheng-Shyuan; Lu, Tsu-Hsiang; Tzeng, Siou-Ling; Wu, Yi-Chan; Wu, Chia-Jung; Lin, Chia-Wei; Hsieh, Ching-Hua
Abstract : Background . This study aims to investigate the effect of feeding low-fat diet (LFD) to diet-induced obesity (DIO) mice lacking TLR5 (TLR5 −/− ), which have a tendency to develop glucose intolerance with increased adiposity, compared to that in C57BL/6 mice. Results . TLR5 −/− and C57BL/6 male mice were divided into three subgroups: (1) control, mice were fed a standard AIN-76A (fat: 11.5 kcal%) diet for 12 weeks; (2) DIO, mice were fed a 58 kcal% high-fat diet (HFD) for 12 weeks; and (3) diet, mice were fed a HFD for 8 weeks to induce obesity and then switched to a 10.5 kcal% LFD for 4 weeks. The glucose intolerance in DIO TLR5 −/− mice was more significant than that in DIO C57BL/6 mice and was not attenuated by a switch to the LFD. Weight-reduction with LFD had significantly decreased the epididymal fat mass in C57BL/6 mice but not in TLR5 −/− mice. In addition, the LFD-fed TLR5 −/− mice showed significantly higher expression of ghrelin in the serum and resistin in the epididymal fat than that in C57BL/6 mice. Conclusions . This study demonstrated that TLR5 gene knockout impairs some effects of weight-reduction in DIO.